Mapping and appraising evidence syntheses of resuscitation training for healthcare professionals: Protocol for a systematic review of reviews - Defi Efendi; Chiyar Edison Sunarya; Mawardi Ihsan; Hazrina Adelia; Nana Rochana; Heni Ekawati; Sholihatul Amaliya; Cho Lee Wong (PLoS ONE, 2026)
Background The number of systematic reviews on resuscitation training has grown rapidly, offering valuable evidence to guide healthcare decision-making. However, methodological shortcomings can compromise validity and yield biased or misleading conclusions. This systematic review aims to systematically map the distribution of published systematic reviews on resuscitation training interventions, evaluate their methodological quality, investigate contextual and methodological factors associated with systematic review quality, and delineate priorities for future systematic reviews. Methods This systematic review protocol follows the PRISMA-P guidelines. A comprehensive search from the inception to August 2025 will be conducted across eight major databases, comprising CENTRAL, EMBASE, MEDLINE, ProQuest, Scopus, Web of Science, CINAHL, and ERIC, to identify published reviews on resuscitation training interventions for healthcare professionals and students, excluding laypersons. All reviews that are appropriate for the inclusion criteria will be screened and selected independently by two reviewers, with disagreements resolved by a third reviewer. Data extraction will cover study characteristics and methodological features, and quality appraisal will be performed using the AMSTAR 2 tool. Findings will be synthesized narratively following the SWiM framework, focusing on methodological rigor and evidence gaps. Conclusion This study will systematically evaluate the methodological quality of published systematic reviews on resuscitation training using the AMSTAR 2 tool, providing key insights to promote higher standards in systematic review conduct and reporting within healthcare education.